The Structure of the Membrane Protein of SARS-CoV-2 Resembles the Sugar Transporter SemiSWEET - Sunil Thomas (Case Western Reserve University, 2020)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the disease COVID-19 that has decimated the health and economy of our planet. The virus causes the disease not only in people but also in companion and wild animals. People with diabetes are at risk of the disease. As yet we do not know why the virus has been highly successful in causing the pandemic within 3 months of its first report. The structural proteins of SARS include membrane glycoprotein (M), envelope protein (E), nucleocapsid protein (N), and the spike protein (S).  Methods: The structure and function of the most abundant structural protein of SARS-CoV-2, the membrane (M) glycoprotein, is not fully understood. Using in silico analyses we determined the structure and potential function of the M protein.  Results: The M protein of SARS-CoV-2 is 98.6% similar to the M protein of bat SARS-CoV, maintains 98.2% homology with pangolin SARS-CoV, and has 90% homology with the M protein of SARS-CoV; whereas, the similarity is only 38% with the M protein of MERS-CoV. In silico analyses showed that the M protein of SARS-CoV-2 has a triple helix bundle, forms a single 3-transmembrane domain, and is homologous to the prokaryotic sugar transport protein SemiSWEET. SemiSWEETs are related to the PQ-loop family whose members function as cargo receptors in vesicle transport, mediate movement of basic amino acids across lysosomal membranes, and are also involved in phospholipase flippase function.  Conclusions: The advantage and role of the M protein having a sugar transporter-like structure is not clearly understood. The M protein of SARS-CoV-2 interacts with S, E, and N protein. The S protein of the virus is glycosylated. It could be hypothesized that the sugar transporter-like structure of the M protein influences glycosylation of the S protein. Endocytosis is critical for the internalization and maturation of RNA viruses, including SARS-CoV-2. Sucrose is involved in endosome and lysosome maturation and may also induce autophagy, pathways that help in the entry of the virus. Overall, it could be hypothesized that the SemiSWEET sugar transporter-like structure of the M protein may be involved in multiple functions that may aid in the rapid proliferation, replication, and immune evasion of the SARS-CoV-2 virus. Biological experiments would validate the presence and function of the SemiSWEET sugar transporter.